Fighting climate change. Local, global: integrating mitigation and adaptation - Locatelli, Bruno (Perspective, 2010)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Since concerns about the present and potential impacts of climate change first emerged, responses have focused more on reducing greenhouse gas (GHG) emissions in the atmosphere, or “mitigation”, than on reducing the vulnerability of societies and ecosystems to climate change, or “adaptation”. Today, climate change is seen as inevitable. Adaptation is therefore becoming increasingly important in international and national policies, as well as in local initiatives. Policies address mitigation and adaptation separately, yet they are complementary and must both be implemented at different levels, from the international to the local. Forests provide an interesting example of how this complementarity could work. Ecosystem services are already recognised and remunerated in mitigation policies (reforestation and soon, perhaps, avoided deforestation). But what about the role of forests in adaptation? How can mitigation and adaptation be linked?"}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Since concerns about the present and potential impacts of climate change first emerged, responses have focused more on reducing greenhouse gas (GHG) emissions in the atmosphere, or “mitigation”, than on reducing the vulnerability of societies and ecosystems to climate change, or “adaptation”. Today, climate change is seen as inevitable. Adaptation is therefore becoming increasingly important in international and national policies, as well as in local initiatives. Policies address mitigation and adaptation separately, yet they are complementary and must both be implemented at different levels, from the international to the local. Forests provide an interesting example of how this complementarity could work. Ecosystem services are already recognised and remunerated in mitigation policies (reforestation and soon, perhaps, avoided deforestation). But what about the role of forests in adaptation? How can mitigation and adaptation be linked?"}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Since concerns about the present and potential impacts of climate change first emerged, responses have focused more on reducing greenhouse gas (GHG) emissions in the atmosphere, or “mitigation”, than on reducing the vulnerability of societies and ecosystems to climate change, or “adaptation”. Today, climate change is seen as inevitable. Adaptation is therefore becoming increasingly important in international and national policies, as well as in local initiatives. Policies address mitigation and adaptation separately, yet they are complementary and must both be implemented at different levels, from the international to the local. Forests provide an interesting example of how this complementarity could work. Ecosystem services are already recognised and remunerated in mitigation policies (reforestation and soon, perhaps, avoided deforestation). But what about the role of forests in adaptation? How can mitigation and adaptation be linked?